Advanced glycation end products in skeletal muscle health and sarcopenia: A systematic review of observational studies. (January 2023) - Granic, Antoneta; Hurst, Christopher; Dismore, Lorelle; Dodds, Richard M.; Witham, Miles D.; Robinson, Sian M.; Sayer, Avan A.
Abstract: Background: Advanced glycation end products (AGEs) and AGEs receptor (RAGE) may play a role in sarcopenia. This systematic review evaluated the associations between AGEs measured in tissues (skin) by autofluorescence (SAF) and/or circulation (blood, urine) and muscle health outcomes (strength, mass, function) and sarcopenia in observational studies. Methods: MEDLINE, Embase, Scopus and Web of Science were searched for studies reporting associations between AGEs and muscle-related outcomes in community-dwelling adults aged ≥ 30 years (until March 2022). Results: Fourteen cross-sectional and one prospective study were included in the narrative summary. SAF was negatively associated with muscle strength, mass, and physical functioning in adults aged ≥ 30 years (four studies), and muscle mass (three studies), strength, and sarcopenia (one study) in adults aged ≥ 65 years. Circulating AGEs were negatively associated with muscle strength and physical functioning (four studies) and predicted the risk of walking disability (one prospective study), and sarcopenia (one study) in older adults. The role of RAGE in muscle health was inconclusive. Conclusions: SAF and circulating AGEs were negatively associated with muscle-related outcomes in adults aged ≥ 30 years in cross-sectional studies. This finding should be confirmed in well-designed prospective studies investigating sarcopenia, as AGEs represent a potentially modifiable target for intervention. Highlights: Advanced glycation-end products (AGEs) may contribute to decline in muscle health. We aimed to update the evidence for the role AGEs in sarcopenia in adults aged ≥ 30. Systematic evaluation of the literature revealed fifteen observational studies. Increased AGEs in skin, blood, or urine were associated with worse muscle function or mass. The role of the receptor for AGEs in muscle health and disease was inconclusive.